2019
DOI: 10.1097/aln.0000000000002909
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative Mechanical Ventilation and Postoperative Pulmonary Complications after Cardiac Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Compared with historic ventilation strategies, modern lung-protective ventilation includes lower tidal volumes (VT), lower driving pressures, and application of positive end-expiratory pressure (PEEP). The contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 56 publications
2
78
0
7
Order By: Relevance
“…1,2 PPCs not only increase the postoperative mortality of patients but also prolong the length of hospital stay and medical costs for patients. 3 For decades, the development of cardiopulmonary bypass and surgical technologies for open-heart surgery has continued to benefit patients with cardiovascular disease, but surgical procedures, extracorporeal circulation, protamine application during surgery, mechanical ventilation, lungs undergoing ischemia-reperfusion, and systemic inflammatory reactions lead to varying degrees of pulmonary complications in patients after cardiac surgery. Faced with pulmonary complications after cardiac surgery, the current prevention and treatment methods have limited effects.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 PPCs not only increase the postoperative mortality of patients but also prolong the length of hospital stay and medical costs for patients. 3 For decades, the development of cardiopulmonary bypass and surgical technologies for open-heart surgery has continued to benefit patients with cardiovascular disease, but surgical procedures, extracorporeal circulation, protamine application during surgery, mechanical ventilation, lungs undergoing ischemia-reperfusion, and systemic inflammatory reactions lead to varying degrees of pulmonary complications in patients after cardiac surgery. Faced with pulmonary complications after cardiac surgery, the current prevention and treatment methods have limited effects.…”
Section: Introductionmentioning
confidence: 99%
“…V T , Pplat and PEEP were not related to patient outcomes, or only related when they influenced the driving pressure. Several retrospective and prospective studies confirmed the importance of driving pressure in ARDS patients [18,19] and surgical patients [12,[20][21][22].…”
Section: Introductionmentioning
confidence: 88%
“…In a cohort study of cardiac surgery patients published in 2019 (n = 4,694), a lung-protective ventilation bundle was applied to 1,913 patients (40.8%) [20]. Postoperative pulmonary complications were reduced by its application (13.9% vs. 6.6%, OR 0.56, 95% CI 0.42 to 0.75).…”
Section: Retrospective Studies For General Surgical Patientsmentioning
confidence: 99%
See 2 more Smart Citations